The Use of Sage Oil Macerates (Salvia officinalis L.) for Oxidative Stabilization of Cod Liver Oil in Bulk Oil Systems - Agnieszka M. Hrebień-Filisińska; Artur Bartkowiak (International Journal of Food Science)
The aim of the study was to investigate the antioxidant properties of sage oil macerates (M) in cod liver oil (CLO) during process oxidation catalyzed by UV radiation. CLO was not only subject to oxidative stabilization but also used as a solvent for active ingredients of sage. Macerates were obtained by combining the sage with CLO, homogenization, maceration, and filtration. The effect of different maceration times (0, 3, 6, 8, 10, 13, and 15 days) and different concentrations of macerate addition (5%, 10%, 25%, and 50%) on the CLO oxidation degree, which was determined by peroxide value (PV), anisidine value (AV), and Totox index, was evaluated. Additionally, the total content of polyphenols in macerates by the Folin-Ciocalteu method, antioxidant activity DPPH, and color was determined. The macerates showed antioxidant properties in CLO. The best effect was shown by the initial macerate (maceration time 0, M0), which in 25% concentration significantly inhibited oxidative processes in CLO. It was also characterized by high content of polyphenols and antioxidant activity of DPPH. Sage macerates can effectively inhibit oxidation of fish oils and prolong their durability.